Animalphabet - Donaldson, Julia; King-Chai, Sharon (New York, NY : Dial Books for Young Readers, 2018)
An immersive book with die-cuts and liftable flaps asks readers to identify a series of animals as they're listed in alphabetical order.
Keywords: Animals -- Juvenile fiction; Alphabet -- Juvenile fiction; Alphabet; Animals; Lift-the-flap books; Toy and movable books; Fiction; Juvenile works; Specimens; Lift-the-flap books; Toy and movable books; Picture books